Nickel on alumina catalysts for the production of hydrogen rich mixtures via the biogas dry reforming reaction: Influence of the synthesis method. (10th August 2015) - Goula, Maria A.; Charisiou, Nikolaos D.; Papageridis, Kiriakos N.; Delimitis, Andreas; Pachatouridou, Eleni; Iliopoulou, Eleni F.
Abstract: Nickel on Al2 O3 supported catalysts with low and high metal loading (8 and 16 wt. %) were synthesized, using the conventional incipient wetness and wet impregnation methods, as well as a slightly modified Equilibrium Deposition Filtration (EDF) technique. Calcined, reduced and used catalysts' properties were determined by applying several characterization techniques such as, N2 adsorption-desorption, ICP-AES, XRD, TEM H2 -TPR and carbon analysis. The catalytic performance for the biogas dry reforming reaction was studied concerning CH4 and CO2 conversion, H2 and CO yield and the produced gas mixture's H2 to CO molar ratio. It was proven that the variation of the synthesis method, affects the catalyst's reducibility, as well as the nickel species' particle size. Catalysts with the low Ni loading present an improved performance when reduced at higher temperature (800 °C). Catalytic behavior was quite different for the 8Ni/Al-edf catalyst, in comparison to the samples prepared by the conventional incipient wetness or wet impregnation methods. Highlights: Variation of synthesis method, affects catalyst's reducibility and performance. TPR experiments confirmed the presence of NiAlx Oy and NiAl2 O4 species. Particle size ranging between 10 and 25 nm for NiAl2 O4 and 5–12 nm for NiO. 8Ni/Al catalysts present improved performance with increasing Treduction . 16Ni/Al catalysts exhibit similar performance regardless synthesis or Treduction .